Review of Heidi M. Altman’s Agency and Bodily Autonomy in Systems of Care (Lexington Books, 2024) - Monika Shehi Herr (Qualitative Research in Medicine & Healthcare, 2024)
Agency and Bodily Autonomy in Systems of Care, edited by Heidi M. Altman (2024), weaves an impressive international tapestry to raise awareness of intercultural factors that restrict or eliminate agency over one’s body in systems of care. It is not often that a book seamlessly strings together stories of people from such seemingly diverse walks of life, including fishermen in the coastal states of Georgia and South Carolina in the U.S., patients in an Italian psychiatric hospital, and people who are deemed overweight in Japan. The merit of the book is that it delivers more than an opportunity for the reader to vicariously visit with different people and places. It ultimately points out the common denominator of the different groups of people it studies, which is their “minoritized social location” (p. 103) as people whose bodies do not meet their societies’ normative expectations and are, therefore, subjected to control.  This control may be applied in different ways, but it always demonstrates the fundamental premise of the book, which is Michele Foucault’s view of “the human body as an element under the control of outside structures, whether they be carceral, military, or medical” (p. 15). [...]